Enhanced and stable strontium and cobalt free A-site deficient La1-xNi0.6Fe0.4O3 (x=0, 0.02, 0.04, 0.06, 0.08) cathodes for intermediate temperature solid oxide fuel cells. (22nd October 2021) - Mei, Wei; Wang, Haojie; Li, Wenlu; Zhou, Juan; Sun, Xiufu; Zhao, Hanwen; Wang, Shimin
Abstract: Perovskite oxides with cobalt and strontium element exhibit severe degradation during the operation for the solid oxide fuel cells (SOFC). Here, we report stable non-cobalt and non-strontium La1-x Ni0.6 Fe0.4 O3 perovskite cathodes with improved oxygen reduction reaction (ORR) activity. A-site deficient La1-x Ni0.6 Fe0.4 O3 cathodes within 8 at.% all exhibit the invariable phase structure with LaNi0.6 Fe0.4 O3 (LNF), and the matched thermal expansion coefficient with that of the (Ce0.90 Gd0.10 )O1.95 (GDC) electrolyte. The polarization resistance of the La0.94 Ni0.6 Fe0.4 O3 (LNF94) cathode is 0.61 Ω cm 2 at 750 °C in air, which is 1/5 of the LaNi0.6 Fe0.4 O3 (2.78 Ω cm 2 ). The peak power density of the corresponding single cell with LNF94 cathode is 0.37 W cm −2 at 750 °C, which is 2.36 times higher than that of the single cell with LNF cathode (0.11 W cm −2 ). We further study the long-term stability of LNF and LNF94 cathodes, the polarization resistance of the LNF94 electrode slightly fluctuates around 0.18 Ω cm 2 during 50 h operation at 800 °C, while the polarization resistance of the LNF increases by about 15%. This work highlights the A-site deficient LNF as an effective and stable non-cobalt and non-strontium cathode for the intermediate temperature solid oxide fuel cells. Highlights: Strontium and cobalt free A-site deficient LaNi0.6 Fe0.4 O3 (LNF) cathode is proposed. La0.94 Ni0.6 Fe0.4 O3 is the optimal chemistry composition among La1-x Ni0.6 Fe0.4 O3 series. The peak power density of the single cell with La0.94 Ni0.6 Fe0.4 O3 cathode reaches 370 mW cm −2 at 750 °C. A-site deficiency enhances ORR activity and long-term stability of LNF cathode.